Analyses of Scores of Examinations for Practical Training in Clinical Skills and for Clinical Training and Scores of Graduation Examinations in Undergraduate Medical Students - TORIMURA, Takuji; OGO, Yoshio; MIYAZAKI, Hiroshi; WATANABE, Masayuki; SATA, Michio; YOSHIDA, Ichiro; HOTTA, Mariko; ABE, Hitoshi; HAYASHI, Akihiro; KOUNO, Syuhei; INUTSUKA, Hiroki; MATUO, Kazuhiko; et al. (Igaku Kyoiku / Medical Education (Japan), 2004)
We analyzed the scores of objective structured clinical examinations (OSCEs) and written examinations administered to fourth-year medical students after practical training in clinical skills and to fifth-year medical students after clinical training and scores of graduation examinations taken by sixth-year medical students. Correlations were analyzed among the scores of 96 students who had taken all 3 examinations during a 3-year period. Mean scores on examinations in the fourth, fifth, and sixth years were compared between sixth-year students who did or did not graduate and between graduating students who did or did not pass the national examination for medical practitioners in Japan. Significant correlations in the scores were found between 1) OSCEs and written examinations for fourth-year students versus those for the fifth-year students; 2) OSCE and written examinations for fourth-year students versus graduation examination scores for the sixth-year students; and 3) OSCE and written examinations for fifth-year students versus graduation examination scores for sixth-year students. In addition, the mean scores in the fourth and fifth years were significantly higher for sixth-year students who graduated and passed the national examination than for students who did not graduate or who graduated but failed the national examination. These results suggest that the practical training in clinical skills given to fourth-year students and the clinical training given to fifth-year students strongly affect the overall evaluation of the ability of sixth-year students and success on the national examination.